Estimating a performance standards adjustment model for workforce programs that provides timely feedback and uses data from only one state - Timothy J. Bartik; Randall Eberts; Ken Kline (W.E. Upjohn Institute for Employment Research, 2009)
The purpose of this paper is to describe a methodology for adjusting performance standards for workforce programs offered by local workforce areas (LWAs). By performance standards adjustment, we mean a model that uses a statistical approach to attempt to better measure the relative performance of different local workforce areas in providing workforce system customers with value added in terms of the systems desired outcomes. Our papers approach has four distinguishing features. First, the performance standards are based on the common measures proposed by the U.S. Department of Labor, which include short- and longer-term employment outcomes. Second, the model is estimated using data from only one state, which allows each state greater flexibility in adapting the adjustment model to the states needs and available data. Third, the model is estimated using data on individual customers, which offers some estimation advantages, particularly when data from only one state is available. Fourth, since some of the common measures are not available until long after the program year is completed, we include real-time predictions of the current performance of the LWA and an assessment of whether or not it will meet its performance standards when the common measure data is eventually available. This more timely feedback on performance provides administrators the opportunity to better manage their operations and offer services that best meet the needs of their customers.
Keywords: J64; J68; 330